Грошові суроґати купецтва у другій половині ХІХ – на початку ХХ ст. - Гуржій, І.; Бойко-Гагарін, А. (Український історичний журнал, 2020)
Мета дослідження полягає у введенні до наукового обігу інформації про раніше невідомих емітентів приватних грошових суроґатів та у встановленні повного ланцюжка їх використання, а також в аналізі практики органів влади асоціювати подібні випуски з фальшивомонетництвом. Методологію визначено загальнонауковими методами і принципами історизму, системності,
об’єктивності, розвитку та багатогранності. Ориґінальність дослідження. Уперше у вітчизняній
історіографії встановлено й описано повний алгоритм і механізм застосування купецтвом власних грошових замінників. Практичне значення досягнутих результатів полягає в можливості застосування їх у наукових студіях із нумізматики, історії економічної думки, грошового обігу, науки
й техніки, криміналістики, а також при підготовці навчально-методичних матеріалів. Основні результати. У 1860-х рр. в окремих місцевостях Російської імперії, господарствах та на виробничих
підприємствах з’явилися приватні грошові замінники (бони, жетони, марки, талони), поява яких
була викликана нестачею розмінної монети. Уряд заборонив випуск локальних грошових суроґатів
у вигляді марок, квитанцій, ярликів та інших знаків чи зобов’язань, що містили у собі необхідність
виплати певної суми товарами або послугами. Відтворюється повний ланцюжок використання приватних бонів. The aim of study is to introduce into the scientific circulation the previously unknown issuers
of the private monetary surrogates and to establish the full chain and mechanism of their use, as well
as to analyze the practice of the imperial government in associating such issues with the counterfeiting.
Research methodology of the article defined by the general scientific methods; the citations of archival
materials and newspaper publications were performed by transcription; the principles of historicism,
systematics, objectivity, development and versatility are applied. The scientific novelty is that for the
first time in the national historiography the complete algorithm and mechanism of the use of the private
monetary substitutes by the merchants during the imperial era are is completely defined and described.
The practical significance of the achieved results lies in the possibility of their application in the next
research areas: numismatics, history of economic, history of the monetary circulation, history of science
and technology, criminalistics, as well as in compiling of the educational and methodological literature.
The main results of the research. In the 1860’s in some regions of the Russian and Austro-Hungarian
Empires in the local farms and manufacturing enterprises has appeared a private money (bonds,
tokens, vouchers, stamps, coupons etc.), the emergence of which was caused by the lack of small coin
denominations for change. A government decree prohibited the use of the local monetary surrogates
in the form of stamps, receipts, labels, tokens and other marks or obligations that were giving an
opportunity for the consumer to get a certain amount of goods or services with paying by this money
substitutes. Analyzing the materials of the historical archives, we managed to recreate and establish the
full chain and the essence of private money of the entrepreneurs who were operating in Ukraine.